TINGKAT KETERAMPILAN DASAR BERMAIN FUTSAL PADA SISWA YANG MENGIKUTI EKSTRAKURIKULER FUTSAL DI MAN 2 PEKANBARU - Putra, Armansyah; Zainur, Zainur; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: The purpose of this study is to illustrate the level of basic skills in playing futsal for students who take part in extracurricular football at MAN 2 Pekanbaru. The location of this research was carried out at MAN 2 Pekanbaru's multi-purpose field which is located at Jl. Diponegoro no. 55, Kelurahan Cinta Raja, Sail District, Pekanbaru City, Riau 28131. Overall the level of basic ability to play futsal is owned by students who take part in extracurricular futsal at MAN 2 Pekanbaru with the following classification: Very good category 0 students 0%, Good Category 6 Students are 42.90%, Enough Category 2 Students are 14.30%, Less Category 5 Students are 35.70%, Less Category 1 Student is 7.14%.Keywords: Basic Futsal Skills Level